Current status and new features of the Consensus Coding Sequence database - Farrell, Catherine M.; O’Leary, Nuala A.; Harte, Rachel A.; Loveland, Jane E.; Wilming, Laurens G.; Wallin, Craig; Diekhans, Mark; Barrell, Daniel; Searle, Stephen M. J.; Aken, Bronwen; Hiatt, Susan M.; Frankish, Adam; et al. (Nucleic acids research, 2014)
The Consensus Coding Sequence (CCDS) project (http://www.ncbi.nlm.nih.gov/CCDS/) is a collaborative effort to maintain a dataset of protein-coding regions that are identically annotated on the human and mouse reference genome assemblies by the National Center for Biotechnology Information (NCBI) and Ensembl genome annotation pipelines. Identical annotations that pass quality assurance tests are tracked with a stable identifier (CCDS ID). Members of the collaboration, who are from NCBI, the Wellcome Trust Sanger Institute and the University of California Santa Cruz, provide coordinated and continuous review of the dataset to ensure high-quality CCDS representations. We describe here the current status and recent growth in the CCDS dataset, as well as recent changes to the CCDS web and FTP sites. These changes include more explicit reporting about the NCBI and Ensembl annotation releases being compared, new search and display options, the addition of biologically descriptive information and our approach to representing genes for which support evidence is incomplete. We also present a summary of recent and future curation targets.